Analisis semantik kata makian dalam novel “Surga untuk Ibuku” karya Riri Ansar - Prasetya, Rahima Wandra (Maliki Interdisciplinary Journal, 2024)
Every word spoken by the characters in the novel is in accordance with the conditions that occurred in that area. In fact, the dirty words in the novel are written clearly, including the many curse words often said by the characters. The aim of this research is to determine the form and meaning of swear words found in the novel Heaven for My Mother. This research was analyzed using descriptive qualitative methods and a library approach, because the data that will be obtained in this research is in the form of sentences. The data source used in this research is the novel Heaven for My Mother by Riri Ansar, focusing on the swear words in it. The data collection technique in this research is observation, namely by reading the novel Heaven for My Mother. The curse word data obtained will be recorded and analyzed for the form and meaning of the word. Then the last one is to compile the results and conclusions. The results of this analysis are seen from their form, so there are 4 words that fall into the category of words, 4 words that are in the form of phrases and 3 words that are in the form of clauses. If you look at the word references, there are 3 categories that fall into swear word references, namely activity references which total 1 word, situation references which total 7 words and references to spirits which total 3 words.